Cannabis legalization in Canada and combatting the illicit cannabis market - Andresen, Matthew (My University, 2024)
Despite the elimination of the illegal cannabis market being a fundamental element to cannabis legalization, as outlined in the Cannabis Act (S.C. 2018, c. 16), the Canadian federal government's efforts have had a mild impact in mitigating its influence. In analyzing possible contributions to the illicit sector's sustainability, these factors are in large part due to the federal government failing to understand consumer behaviours in recreational cannabis usage, as evidenced by lack of accommodation for frequent users, pricing and quality of legal cannabis compared to illegal cannabis, alongside faulty enforcement of cannabis law due to issues of conciseness and discretionary powers between the police and federal government. However, there are some suggestions that could better help the federal government in achieving its goal of combatting the illegal cannabis market. The potential amendments to cannabis policy include lowering tax on legal cannabis to better compete with illegal cannabis at the market level while refocusing on addressing public health concerns through promoting the safety of legal cannabis, controlling accessibility of legal cannabis, and providing public education regarding cannabis consumption. If done correctly, each amendment made would address the flaws within cannabis policy, allowing the Canadian federal government to combat the illegal cannabis market more efficiently.
Keywords: cannabis; federal government policies; Canada